Tata Laksana ‘Behavioral Activation’ untuk Menurunkan Tingkat Depresi pada Pasien Stroke - Ima Santika Jayati; M. Noor Rochman Hadjam (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
Depression  in  patients  of  stroke causes  a  decrease  in  health,  quality  of  life,  and positive feelings. Behavioral Activation (BA) is a technique that consists of various series of activities  that  can  increase  happiness,  productivity, and patient's  meaning  of  life.  BA  for depression in stroke patients still needs to be developed more in clinical setting. Therefore, we  need  a  treatment  guideline  for  psychologists  in  conducting  assessment, diagnosis,  and treatment for depression in stroke patients based on BA principles. This study aims to verify the  effectiveness  of  BA  guideline  by  evaluating psychologist’s self efficacy in delivering service for stroke patients, patients’ satisfaction of service, & patients’ BDI scores. Data were analyzed by visual inspection and qualitative analysis.